A népi-fasiszta Európa - Pohl, Dieter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The article discusses the rise of fascism and völkisch ethnonationalism in Europe, particularly during the 1930s, leading up to and including World War II. It highlights how various European countries experienced a rightward political shift, with fascist and ethnonationalist movements growing out of the post-World War I environment. These movements were characterized by ultranationalism, anti-communism, and a high propensity for violence. The text argues that the political landscape of the era was shaped not just by fascism but by a blend of fascist and ethnonationalist tendencies, which varied across different political systems. It also emphasizes the role of anti-Semitism as a unifying factor among ethnonationalist groups and describes the transformation of traditional authoritarian regimes into ones that embraced these new ideologies. Lastly, the text examines specific countries like Hungary and Romania, detailing how local political dynamics and international influences led to the rise of extreme right-wing movements, culminating in the cooperation or conflict with Nazi Germany’s expansionist policies.